Diagnostic and Therapeutic Approach to Epidermoid Cysts in the Gluteal Region: A Rare Case and Review of the Literature (Global Journal of Medical Research, 2023)
Epidermoid cysts of the gluteal region are rare benign tumors that are often difficult to diagnose However the diagnosis depends mainly on histology which remains the most reliable diagnostic tool for epidermoidcysts We present the case of a 63-year-old woman with no notable pathological history who presented with a right gluteal mass The cystwas surgically excised and the diagnosis was confirmed by histopathologic examination We discuss the clinical features and possible etiology of this rare c ondition as well as the importance of medical imaging for an accurate diagnosis Epidermoidcysts are often asymptomatic but may cause discomfort or pain in the area where they are found When they are located in the gluteal area and can be confused with other types of cysts such as lipomas or sebaceous cysts
Keywords: epidermoid cyst; gluteal region; excision surgery; histology; medical imaging; diagnosis